Chloramphenicol Mitigates Oxidative Stress by Inhibiting Translation of Mitochondrial Complex I in Dopaminergic Neurons of Toxin-Induced Parkinson's Disease Model. (26th August 2019) - Han, Jeongsu; Kim, Soo Jeong; Ryu, Min Jeong; Jang, Yunseon; Lee, Min Joung; Ju, Xianshu; Lee, Yu Lim; Cui, Jianchen; Shong, Minho; Heo, Jun Young; Kweon, Gi Ryang
Abstract : Paraquat (PQ), an herbicide considered an environmental contributor to the development of Parkinson's disease (PD), induces dopaminergic neuronal loss through reactive oxygen species (ROS) production and oxidative stress by mitochondrial complex I. Most patients with PQ-induced PD are affected by chronic exposure and require a preventive strategy for modulation of disease progression. To identify drugs that are effective in preventing PD, we screened more than 1000 drugs that are currently used in clinics and in studies employing PQ-treated cells. Of these, chloramphenicol (CP) showed the most powerful inhibitory effect. Pretreatment with CP increased the viability of PQ-treated SN4741 dopaminergic neuronal cells and rat primary cultured dopaminergic neurons compared with control cells treated with PQ only. CP pretreatment also reduced PQ-induced ROS production, implying that mitochondrial complex I is a target of CP. This effect of CP reflected downregulation of the mitochondrial complex I subunit ND1 and diminished PQ recycling, a major mechanism of ROS production, and resulted in the prevention of cell loss. Notably, these effects of CP were not observed in rotenone-pretreated SN4741 cells and Rho-negative cells, in which mitochondrial function is defective. Consistent with these results, CP pretreatment of MPTP-treated PD model mice also ameliorated dopaminergic neuronal cell loss. Our findings indicate that the inhibition of mitochondrial complex I with CP protects dopaminergic neurons and may provide a strategy for preventing neurotoxin-induced PD.